Volume 5: Turbo Expo 2004, Parts a and B 2004
DOI: 10.1115/gt2004-53544
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Blade Sweep on the Energetic Behavior of Axial Flow Turbomachinery Rotors at Design Flow Rate

Abstract: Experimental and computational studies were carried out in order to survey the energetic aspects of forward and backward sweep in axial flow rotors of low aspect ratio blading for incompressible flow. It has been pointed out that negative sweep tends to increase the lift, the flow rate and the ideal total pressure rise in the vicinity of the endwalls. Just the opposite tendency was experienced for positive sweep. The local losses were found to develop according to combined effects of sweep near the endwalls, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…9 (a), solid line represents the reference blade. It is noted that a backward-swept blade is more effective in increasing the adiabatic efficiency, which has been reported in the previous study (9) . Distributions of total pressure, total temperature and adiabatic efficiency for the reference and the optimized shapes, which are tangentially averaged at the exit of the rotor, are shown along the spanwise direction in Figs.…”
Section: Optimization Of Rotor Bladessupporting
confidence: 52%
See 1 more Smart Citation
“…9 (a), solid line represents the reference blade. It is noted that a backward-swept blade is more effective in increasing the adiabatic efficiency, which has been reported in the previous study (9) . Distributions of total pressure, total temperature and adiabatic efficiency for the reference and the optimized shapes, which are tangentially averaged at the exit of the rotor, are shown along the spanwise direction in Figs.…”
Section: Optimization Of Rotor Bladessupporting
confidence: 52%
“…They showed that the stall margin was significantly improved with the forward swept blade although a very little change in the peak efficiency was produced by the blade sweep or lean. In addi-tion, Janos Vad, et al (9) studied experimentally as well as numerically the aspects of forward-and backward-sweep in axial flow rotors having low aspect ratio blade for incompressible flow. Their studies showed that the forwardswept bladed rotor reduces total efficiency compared to the unswept and backward-swept bladed rotors.…”
Section: Introductionmentioning
confidence: 99%
“…The performance and loss modifying aspects of forward sweep/skew, which are specific to the individual case studies as the above literature overview suggests, are closely related to the three-dimensional (3D) features of the blade passage flow [12,14,15]. Such 3D flow features are especially characteristic for rotors of CVD, due to the spanwise blade circulation gradient and the resultant vorticity shed from the blade [2].…”
Section: Introductionmentioning
confidence: 95%
“…Above this threshold, only moderate efficiency improvement is expected. Since the fan efficiency is closely related to the lift and drag of the blade sections (14) , the above yield that only minor changes are expected in c L and c D of a blade section -or of an airfoil being in aerodynamic analogy with the blade section -above Reynolds number ≈ 150 000. Indeed, as the data in Ref.…”
Section: Wind Tunnel Experimentsmentioning
confidence: 99%